2011
DOI: 10.1007/s10712-011-9112-8
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for Century-Timescale Acceleration in Mean Sea Levels and for Recent Changes in Extreme Sea Levels

Abstract: Two of the most important topics in Sea Level Science are addressed in this paper. One is concerned with the evidence for the apparent acceleration in the rate of global sea level change between the 19 th and 20 th centuries and, thereby, with the question of whether the 20 th century sea level rise was a consequence of an accelerated climate change of anthropogenic origin. An acceleration is indeed observed in both tide gauge and saltmarsh data at different locations around the world, yielding quadratic coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 67 publications
0
73
0
1
Order By: Relevance
“…However, extreme WL exhibit long-term trends that cannot be ignored. Over the 20th century, these trends have been shown to be similar to those of mean sea level (MSL) at most locations worldwide (Woodworth et al, 2011). To account for this behaviour in the systematic data set, the linear trend is calculated for the entire tide-gauge record and removed from the data.…”
Section: Likelihood Formulationmentioning
confidence: 99%
“…However, extreme WL exhibit long-term trends that cannot be ignored. Over the 20th century, these trends have been shown to be similar to those of mean sea level (MSL) at most locations worldwide (Woodworth et al, 2011). To account for this behaviour in the systematic data set, the linear trend is calculated for the entire tide-gauge record and removed from the data.…”
Section: Likelihood Formulationmentioning
confidence: 99%
“…For example, the vertical stability of the Australian continent and its suitability as a datum for MSL observations has been debated for decades [e.g., Emery, 1986, 1988;Bryant et al, 1988;Amin, 1993;Belperio, 1993;Feng et al, 2004;Sandiford, 2007;Moucha et al, 2008;Watson, 2011;Lewis et al, 2012]. Hay et al [2015], Haigh et al [2014], Hogarth [2014], Holgate and Woodworth [2004], Jevrejeva et al [2014], Jorda [2014], Merrifield et al [2009], Olivieri and Spada [2013], Watson et al [2015], and Woodworth et al [2009Woodworth et al [ , 2011; those that claim deceleration include Boretti [2012], Boretti and Watson [2012], Parker et al [2013], and Watson [2011]; those that claim neither include Schr€ oter [2010, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in regional extreme sea levels have been related mostly to changes in the mean sea level, storm surges and wind set-up (Marcos et al, 2009;Lowe et al, 2010;Woodworth et al, 2011b). However, in a recent study of water levels from tide gauges, Merrifield et al (2013) identified, apart from tidal and seasonal components, non-tidal residual components as an important contribution to annual maximum water levels.…”
Section: Introductionmentioning
confidence: 99%